The Concept of Islamic Education in Strengthening Children's Independence - Rita Hartati; Samwil Samwil; Sulaiman Ali (IJELR: International Journal of Education, Language, and Religion, 2020)
This article aims to discuss the basic concept of strengthening children’s independence within the paradigm of Islamic education. Specifically, this study focuses on the child's self-reliance factors, the method, and the benefits of strengthening children’s independence according to the concept of Islamic education. We argue that self-independence is important for children future life. It affects the mentality and the quality of upbringing that determines the ability of the child. Parents should be able to build and ensure that the parental values are infused within children belief system as a capital in their next life. Among the many methods of strengthening children's independence are Targhipand Tarhib. These methods is generally about letting the child to take part in the decision making process.